ANALISIS PENJADWALAN SISTEM PERAWATAN MESIN MOLDING PADA PT KWONG FAI DI KOTA BATAM - nababan, rolan marcos; Paskaria Loyda Tarigan, Elsya (LPPM Universitas Putera Batam, 2023)
In industrial companies to maintain company performance, smooth production is very important in every business, especially in manufacturing. The machine is one of the production factors that affect the smooth production process. The production process at PT KWONG FAI BATAM experienced a lot of machine downtime which resulted in the production process not running smoothly. This study aims to determine the machine maintenance scheduling intervals to minimize machine downtime. Reliability Centered Maintenance II with calculations of Failure Mode and Effect Analysis, MTTF, and MTTR methods used in this study. This study uses downtime data starting from July 2021 to December 2020. The results of this study obtained that the FMEA on Serial Machine 01, Serial Machine 02, and Serial Machine 05 maintenance repair dirty mold activities are maintenance repair activities with the highest or most frequent frequency based on the calculation of the RPN. maintenance intervals on Serial Machines that have the highest downtime rate include Serial Machine No. 05 Preventive Maintenance activities are carried out with maintenance intervals of 3.24 hours, Machine Serial No. 02 maintenance intervals of 105.81 hours, and Machine Serial No. 01 Preventive Maintenance activities are carried out at intervals of 13.57 hours.